2012
DOI: 10.1111/j.1399-3054.2012.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Polygonum sachalinense alters the balance between capacities of regeneration and carboxylation of ribulose‐1,5‐bisphosphate in response to growth CO2 increment but not the nitrogen allocation within the photosynthetic apparatus

Abstract: The limiting step of photosynthesis changes depending on CO(2) concentration and, in theory, photosynthetic nitrogen use efficiency at a respective CO(2) concentration is maximized if nitrogen is redistributed from non-limiting to limiting processes. It has been shown that some plants increase the capacity of ribulose-1,5-bisphoshate (RuBP) regeneration (evaluated as J(max) ) relative to the RuBP carboxylation capacity (evaluated as V(cmax) ) at elevated CO(2) , which is in accord with the theory. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…These parallel increases were likely associated with the maintenance of a close functional balance between carboxylation and electron transport events (J max /V cmax ), which seemed to be conserved among coffee genotypes and irrespective of growth [CO 2 ] (Table 2). Similar results have been reported for some acacia species [17,60] and also in other plant species, where the unchanging J max /V cmax ratio has been interpreted as reflecting an absence of resource redistribution among photosynthetic components [61]. Additionally, the reinforcement of photosynthetic components under high [CO 2 ] was also unrelated to changes in photochemical efficiency as analyzed by Chl a fluorescence.…”
Section: Discussionsupporting
confidence: 84%
“…These parallel increases were likely associated with the maintenance of a close functional balance between carboxylation and electron transport events (J max /V cmax ), which seemed to be conserved among coffee genotypes and irrespective of growth [CO 2 ] (Table 2). Similar results have been reported for some acacia species [17,60] and also in other plant species, where the unchanging J max /V cmax ratio has been interpreted as reflecting an absence of resource redistribution among photosynthetic components [61]. Additionally, the reinforcement of photosynthetic components under high [CO 2 ] was also unrelated to changes in photochemical efficiency as analyzed by Chl a fluorescence.…”
Section: Discussionsupporting
confidence: 84%
“…However, experimental data do not always support this prediction (e.g. Akita et al , 2012). Furthermore, our model also showed that the increase in the J max25 : V c,max25 ratio in response to the elevated CO 2 became smaller at a lower temperature (results not shown), suggesting a strong interaction between CO 2 and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…A lower soil N content could result in smaller chloroplasts 31 , leading to a decreased chloroplast surface area facing the intercellular air spaces 32 and an increased distance between the intercellular space and the catalytic site of Rubisco 12 . Adding N to the soil could improve the leaf N content in the Rubisco, bioenergetics, and light-harvesting components 7,3335 , but the changes in the proportion of N in these components were unclear 1,11 .…”
Section: Introductionmentioning
confidence: 99%